2012
DOI: 10.1016/j.pain.2012.01.032
|View full text |Cite
|
Sign up to set email alerts
|

Changes in regional gray matter volume in women with chronic pelvic pain: A voxel-based morphometry study

Abstract: Chronic pelvic pain (CPP) is a highly prevalent pain condition, estimated to affect 15-20% of women in the United States. Endometriosis is often associated with CPP, however other factors, such as pre-existing or concomitant changes of the central pain system, might contribute to the development of chronic pain. We applied voxel-based morphometry to determine whether women with CPP with and without endometriosis display changes in brain morphology in regions known to be involved in pain processing.Four subgrou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
160
1
9

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 216 publications
(179 citation statements)
references
References 42 publications
9
160
1
9
Order By: Relevance
“…42 Women with endometriosis-associated chronic pelvic pain displayed decreased gray matter volume in brain regions involved in pain perception. 35 In mice with adenomyosis that was induced in the same manner as in this study, we have shown that, starting from just 1 month after the induction, the mice exhibit progressively deteriorating hotplate latency as compared with mice without the induction. 9,10 Our finding that EGCG treatment improved the GABAergic inhibition of pain seems to be consistent with the report that EGCG has anxiolytic effects that could result from an interaction with GABA A receptors.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…42 Women with endometriosis-associated chronic pelvic pain displayed decreased gray matter volume in brain regions involved in pain perception. 35 In mice with adenomyosis that was induced in the same manner as in this study, we have shown that, starting from just 1 month after the induction, the mice exhibit progressively deteriorating hotplate latency as compared with mice without the induction. 9,10 Our finding that EGCG treatment improved the GABAergic inhibition of pain seems to be consistent with the report that EGCG has anxiolytic effects that could result from an interaction with GABA A receptors.…”
Section: Discussionsupporting
confidence: 54%
“…33 Future studies are needed to determine as whether the decreased number of GAD65-expressing neurons is the result of induced adenomyosis, neonatal dosing of tamoxifen, or both. Since women with primary dysmenorrhea are shown to have changed brain metabolism 34 and women with endometriosis-associated chronic pelvic pain display decreased gray matter volume in brain regions involved in pain perception, 35 it is biologically plausible that induced adeomyosis alone could cause loss of GABAergic inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…85 Second, brain volume was investigated in 4 groups of women: (1) healthy controls, (2) women with CPP without endometriosis, (3) women with CPP and endometriosis, and (4) women with endometriosis but no associated pain. 86 Perhaps unsurprisingly, women with CPP had alterations in gray matter volume consistent with findings in other chronic pain conditions, 87 whether they had endometriosis. However, more interestingly, the women with endometriosis but no pain had an increased volume of the periaqueductal gray, a key region of the descending pain modulatory system (DPMS).…”
Section: Painmentioning
confidence: 65%
“…However, it is unclear whether these alterations in GM volume acted as a predisposing factor or a secondary effect caused by disease-related conditions. Various types of chronic pain consist of another condition that is also frequently related to personality and mood changes of the patient, specifically anxiety and depression (Burgmer et al, 2009;Seminowicz et al, 2011;As-Sanie et al, 2012;Khan et al, 2014). VBM is a method of assessing brain GM volume that has previously been applied to various chronic pain conditions (Apkarian et al, 2004;Draganski et al, 2006;May, 2008;Younger et al, 2010;As-Sanie et al, 2012;Khan et al, 2014).…”
Section: Discussionmentioning
confidence: 99%